Squamous Cell Carcinoma of the Eyelids. A Case Report - Mariela Julia Curbelo Gómez; Maykelín Rodríguez Pérez; Daniel Martínez Ojeda; Beatriz Sánchez Curbelo (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2016)
From a clinical point of view, many neoplastic and pseudoneoplastic lesions of the eyelids and conjunctiva can be confused. Consequently, a pathological examination must be performed to establish the correct diagnosis and treatment. We present the case of an 84-year-old woman treated at the Ophthalmology Department of Dr. Gustavo Aldereguía Lima Hospital in Cienfuegos due to ulcerated and vascularized lesions on the inner part of the upper lid and the head of the right eyebrow and left lower lid. The biopsy revealed a squamous cell carcinoma. A wide excision of the affected region was performed and the entire area was reconstructed using the Tenzel technique to improve the patient's quality of life. This case is of interest given the bilateral presentation of the carcinoma.